Transforming Women's Education - Smith, Jewel A. (University of Illinois Press, 2022)
Female seminaries in nineteenth-century America offered middle-class women the rare privilege of training in music and the liberal arts. A music background in particular provided the foundation for a teaching career, one of the few paths open to women. Jewel A. Smith opens the doors of four female seminaries, revealing a milieu where rigorous training focused on music as an artistic pursuit rather than a social skill. Drawing on previously untapped archives, Smith charts women's musical experiences and training as well as the curricula and instruction available to them, the repertoire they mastered, and the philosophies undergirding their education. She also examines the complex tensions between the ideals of a young democracy and a deeply gendered system of education and professional advancement. An in-depth study of female seminaries as major institutions of learning, Transforming Women's Education illuminates how musical training added to women's lives and how their artistic acumen contributed to American society.